Cyclic AMP/PKA-Promoted Apoptosis: Insights from Studies of S49 Lymphoma Cells - Insel, P. A.; Wilderman, A.; Zhang, L.; Keshwani, M. M.; Zambon, A. C. (Hormone and Metabolic Research, 2014)
Increases in cyclic AMP (cAMP) are pro-apoptotic in numerous cell types, but the mechanisms of cAMP-promoted apoptosis are poorly defined. We have used murine S49 T-lymphoma cells as a model to provide insight into these mechanisms. Increases in cAMP in wild-type (WT) S49 cells were first noted to kill these cells in the 1970 s, but only in recent years, it was shown that this occurs by the intrinsic (mitochondria-dependent) apoptotic pathway. The apoptotic response does not occur in protein kinase A-null (kin-) clonal variants of WT S49 cells and thus is mediated by protein kinase A (PKA). A second S49 clonal variant, cAMP-Deathless (D-), has PKA activity but lacks cAMP-promoted apoptosis. Apoptosis in WT S49 cells occurs many hours after cAMP/PKA-promoted G1 cell cycle arrest and involves increased expression of Bim, a pro-apoptotic member of the Bcl-2 (B-cell lymphoma-2) family. This increase in Bim expression does not occur in kin- or D- S49 cells and knockdown of Bim blunts cAMP-mediated apoptosis in WT cells. Cytotoxic T lymphocyte antigen-2 also appears to contribute to cAMP/PKA-promoted apoptosis of S49 cells. Based on time-dependent differences in gene expression between WT, D- and kin- S49 cells following incubation with 8-(4-chlorophenylthio)-cAMP, additional genes and proteins are likely involved in this apoptosis. Studies with S49 cells should reveal further insight regarding the mechanisms of cAMP/PKA-promoted cell death, including the identification of proteins that are targets to enhance (e. g., in cancer) or inhibit (e. g., cardiac failure) apoptosis in response to hormones, neurotransmitters, and drugs.
Keywords: kin-; BIM; CTLA-2; glucocorticoids; forskolin